2015
DOI: 10.1103/physrevb.91.134114
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of nanosecond infrared laser-induced breakdown in water: Evidence for multiphoton initiation via an intermediate state

Abstract: Investigation of the wavelength dependence (725 -1025 nm) of the threshold for nanosecond optical breakdown in water revealed steps consistent with breakdown initiation by multiphoton ionization, with an initiation energy of about 6.6 eV. This value is considerably smaller than the autoionization threshold of about 9.5 eV, which can be regarded as band gap relevant for avalanche ionization. Breakdown initiation is likely to occur via excitation of a valence band electron into a solvated state, followed by rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 64 publications
8
91
0
1
Order By: Relevance
“…Studies on I th (λ) for IR nanosecond (ns) breakdown confirmed MPI initiation of AI [15,16]. In fs breakdown, seed electrons for AI are abundant, and SFI can contribute significantly to the free electron density reached at the end of the laser pulse.…”
Section: Sfi Consists Of Multiphoton Ionization (Mpi) and Tunneling Imentioning
confidence: 96%
See 1 more Smart Citation
“…Studies on I th (λ) for IR nanosecond (ns) breakdown confirmed MPI initiation of AI [15,16]. In fs breakdown, seed electrons for AI are abundant, and SFI can contribute significantly to the free electron density reached at the end of the laser pulse.…”
Section: Sfi Consists Of Multiphoton Ionization (Mpi) and Tunneling Imentioning
confidence: 96%
“…More specifically, femtosecond laser-induced optical breakdown in water and aqueous media enables to perform highly precise surgery on cells [1][2][3] and within transparent biological tissues [4][5][6][7][8]. The dependence of optical breakdown thresholds on laser parameters provides information about breakdown mechanisms such as the interplay of strong-field ionization (SFI) and avalanche ionization (AI) [9][10][11][12][13][14], as well as about the band structure of the breakdown medium and the mechanisms of breakdown initiation [15,16]. Detailed knowledge of the parameter dependence of breakdown thresholds is, furthermore, important for material processing and laser surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the multiphoton ionization process, bound electrons may absorb several laser photons simultaneously to overcome their ionization potential [7]. N. Linz et al showed that in nanosecond LIB, the avalanche ionization is the most responsible mechanism for the electron excitation [8]. In non-distilled water, the seed electrons for avalanche ionization mainly come from thermal excitation of the impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Laser parameters such as wavelength, pulse duration, fluence and the choice of the target material (solid, liquid and gas) can strongly influence the efficiency of conversion of laser energy into plasmas [6].There are many reports in studying dynamics of optical breakdown process in water as a good dielectric [8], [11]- [16], [21], [22]. However, to our best knowledge there is no report on studying dynamics of optical breakdown process in water as an environment for colloidal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…11,[14][15][16] Briefly, atoms are ionized through multiphoton or tunneling ionization within the focal zone of a high-intensity laser pulse. Free electrons can then absorb more photons through inverse-Bremsstrahlung absorption, gaining sufficient kinetic energy to ionize even more atoms during subsequent collisions.…”
Section: Finesse Of Transparent Tissue Cutting By Ultrafast Lasers Atmentioning
confidence: 99%